Patient‐provider discussions of bariatric surgery and subsequent weight changes and receipt of bariatric surgery. Issue 8 (10th June 2021) - Chang, Lee‐Shing; Malmasi, Shervin; Hosomura, Naoshi; Zhang, Huabing; Brown, C. Justin; Lei, Victor J.; Rubin, Alexa; Ting, Clara; Tong, Kimhouy; Shubina, Maria; Turchin, Alexander
Abstract: Objective: The purpose of this study was to determine whether patients who discuss bariatric surgery with their providers are more likely to undergo the procedure and to lose weight. Methods: A retrospective cohort study of adults with BMI ≥ 35 kg/m 2 treated between 2000 and 2015 was conducted to analyze the relationship between a discussion of bariatric surgery in the first year after study entry and weight changes (primary outcome) and receipt of bariatric surgery (secondary outcome) over 2 years after study entry. Natural language processing was used to identify the documentation of bariatric surgery discussion in electronic provider notes. Results: Out of 30, 560 study patients, a total of 2, 659 (8.7%) discussed bariatric surgery with their providers. The BMI of patients who discussed bariatric surgery decreased by 2.18 versus 0.21 for patients who did not ( p < 0.001). In a multivariable analysis, patients who discussed bariatric surgery with their providers lost more weight (by 1.43 [change in BMI]; 95% CI: 1.29‐1.57) and had greater odds (10.2; 95% CI: 9.0‐11.6; p < 0.001) of undergoing bariatric surgery. Conclusions: Clinicians rarely discussed bariatric surgery with their patients. Patients who did have this discussion were more likely to lose weight and to undergo bariatric surgery.